Improving sensitivity and duty-cycle of a double torsion pendulum. (28th May 2019) - Bassan, M; De Laurentis, M; De Rosa, R; Di Fiore, L; Errico, L; Garufi, F; Grado, A; Minenkov, Y; Pucacco, G; Spagnuolo, V; Stanga, R; Visco, M
Abstract: In this paper the enhancement of the sensitivity and of the duty-cycle of a double stage suspended torsion pendulum are described. The increase in sensitivity, both for force and torque measurements, was obtained rearranging the pendulum mechanics, reducing the value of the suspended masses and moments of inertia and by adopting additional read-outs based on optical levers. The improvement of the duty-cycle was obtained by controlling the suspension point of the pendulum to reduce the effect of seismic noise on the translation resonances of the system. The reduction of these motions allowed continuous operation for three weeks, in high sensitivity regime of the read-out electronics, resulting in a force sensitivity of and a torque sensitivity of around 10 mHz.